Malignancy Rate in Thyroid Nodules with Atypia or Follicular Lesion of Undetermined Significance - Pasha, Hamdan Ahmed; Dhanani, Rahim; Mughal, Ainulakbar; Ahmed, Kaleem S.; Suhail, Anwar (International Archives of Otorhinolaryngology, 2020)
Introduction Atypia of undetermined significance (AUS) or follicular lesion of undetermined significance (FLUS) is one of the six diagnostic categories of the Bethesda System for Reporting Thyroid Cytopathology. The prevalence of malignancy among Bethesda category III cytology is variable, ranging from 5% to 37% in the literature.Objective To determine the rate of malignancy in thyroid nodules reported as Bethesda category III.Methods A total of 495 patients underwent surgical intervention for thyroid nodules from January 2015 to December 2017. The present study included 81 cases reported as Bethesda category III, and their medical records were reviewed.Results Out of 495 fine-needle aspiration cytology samples, 81 (16.4%) samples were labeled as AUS/FLUS. Among these 81 patients, the mean age was 43.0 years (± 13.9), with only 11 (14%) patients older than 55 years of age. Most of our patients were female (n = 69; 85.2%), and the rest were male. The rate of malignancy based on the final histology was of 33.3% (n = 27). The majority were 17 cases (21%) of papillary carcinoma, followed by follicular carcinoma (n = 6) (7.4%).Conclusion The risk of malignancy can be higher than it is commonly believed, and guidelines should be based on the data from the institutions themselves for a better assessment of the outcomes.
Keywords: atypia of undetermined significance; thyroid nodule; bethesda; fine-needle aspiration